JURIDICAL ANALYSIS OF PRICE FIXING AS UNFAIR BUSINESS COMPETITION - Henry Aspan; Etty Sri Wahyuni; Ari Prabowo; Ami Natuz Zahara (Universitas Efarina, 2025)
Price fixing is one of the prohibited agreements under competition law due to its inherently anti-competitive nature and harm to consumers. This research aims to analyze price fixing regulations under Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, focusing on the application of per se illegal approach, evidence using indirect evidence, and law enforcement challenges in Indonesia. The research method used is normative juridical with statutory, conceptual, and case study approaches. The results show that price fixing is regulated under Article 5 of Law No. 5 of 1999 with a per se illegal approach that does not require proof of impact. However, in practice, the Business Competition Supervisory Commission (KPPU) often faces difficulties in proof as business actors tend to avoid written agreements. The use of indirect evidence consisting of economic and communication evidence has become an increasingly developed alternative proof. This research recommends strengthening regulations regarding the position of indirect evidence and enhancing KPPU's capacity in economic analysis for effective competition law enforcement.